Pustakawan Guru sebagai Agen Literasi Informasi di Sekolah Madania Parung Bogor - Azrina, Okta; Kesuma, Mezan el-Khaeri; Nurjannah, Latief (UIN Raden Intan Lampung, 2022)
This paper aims to analyze the role of teacher librarians as agents of information literacy at Madania Parung Elementary School, Bogor. Librarians are information literacy agents in libraries. As the